2021
DOI: 10.1259/dmfr.20210023
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of an MRI-based radiomics nomogram for distinguishing Warthin’s tumour from pleomorphic adenomas of the parotid gland

Abstract: Objective: Preoperative differentiation between parotid Warthin’s tumor (WT) and pleomorphic adenoma (PMA) is crucial for treatment decisions. The purpose of this study was to establish and validate an MRI-based radiomics nomogram for preoperative differentiation between WT and PMA. Methods and materials: A total of 127 patients with histological diagnosis of WT or PMA from two clinical centres were enrolled in training set (n = 75; WT = 34, PMA = 41) and external test set (n = 52; WT = 24, PMA = 28). Radiomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 38 publications
1
13
2
Order By: Relevance
“…For differentiation of PA from WT, our study found that the radiomics nomogram incorporating radiomics features, age, and sex exhibited slightly better results than the radiomics nomogram used by Zheng et al (36). Radiomics feature-based ADC also plays an important role in the final radiomics model.…”
Section: Discussionmentioning
confidence: 60%
“…For differentiation of PA from WT, our study found that the radiomics nomogram incorporating radiomics features, age, and sex exhibited slightly better results than the radiomics nomogram used by Zheng et al (36). Radiomics feature-based ADC also plays an important role in the final radiomics model.…”
Section: Discussionmentioning
confidence: 60%
“…It can also contribute to predict the prognosis in some instances [15][16][17]. Several recent articles have explored the value of radiomics, clinical, and their combined models for the classification of PA, WT, and malignancy [18][19][20][21][22]. However, the selection of clinical factors is not uniform.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics features were extracted from axial T1W and T2W sequences. The authors found that the radiomics signature had a notable predictive value in differentiating parotid Warthin tumors from PMA, with an AUC of 0.953 and 0.918 for the training and test sets, respectively [36 ▪ ]. In another study, Zheng et al [37 ▪ ] applied clinical factors and radiomics signatures to logistic regression analysis for differential diagnosis of 60 benign and 55 malignant PGTs by T1W and T2W MRI sequences.…”
Section: Radiomics and Deep Learning Applications In Differential Dia...mentioning
confidence: 99%